Acoustic impedance variations of Helmholtz resonators of two plates with orifices inlet neck against the distance between the plates - Birnbach, M.; Śliwiński, A.; Zachara, S. (Archives of Acoustics, 2004)
Experimental examinations of acoustic impedance of complex Helmholtz resonators of two plates with orifices inlet neck using Kundt tube procedure were performed. Few variants of model resonators were studied depending on the number of orifices (and their diameters) in the plates and against variations of the distance between the plates for a constant volume of the resonator cavity. A regular dependence of the acoustical impedance as well as the absorption coefficient against the distance between the inlet cover plates was observed for a given configuration of the orifices. Changes of the configuration (number of orifices their size and plane distribution in both plates and the relation between the lower and the upper one design) caused evident variations in acoustical properties, however no regular dependence could be found. Some configurations are more optimal than the others.